Demands of Expanding Populations and Development Planning Clean Air, Safe Water, Fertile Soils - Siegel, Frederic R. (Springer Berlin Heidelberg : Imprint: Springer, 2008)
This book brings together three topics that interact to affect the quality of life on Earth. First, it examines expanding populations (and contracting ones) in regional and national contexts. Second, the book reviews the impacts of pollution on people, ecosystems and economic ventures. The rate of population increase is slowing but growth momentum is projected to carry the Earth's population from >6.6 billion in 2007 to 9.2-11 billion inhabitants by 2050. Vast numbers of today's world population, mainly in less developed or developing nations, suffer illnesses from chemical or biological pollutants in the air they breathe, the water they drink, and the foods they consume. Millions die. What then can be expected for a 50% larger population by 2050? Third, the book asserts that well-planned development projects adhering to environmental laws and with best available technologies, will reduce ecosystem pollution yet yield strong profit margins. Proactive project design will also carry social development aims such as in education, job creation, and healthcare. The text includes examples of pollution from human activities and reviews solutions to alleviate or eliminate them.